A remark on material parameter identification using finite elements based on constitutive models of evolutionary-type - Hartmann, Stefan (Computer Assisted Methods in Engineering and Science, 2017)
In this paper, we show that sensitivity analysis in connection with material parameter identification problems – using implicit finite elements of quasi-static problems on the basis of evolutionary-type constitutive equations – is related to simultaneous sensitivity equations and internal numerical differentiation. Thus, this study mainly focuses on investigating how these approaches are connected to the solution procedures based on finite elements. In addition, we discuss how to consider reaction forces in the sensitivity analysis, as this aspect is often neglected despite the fact that experimental results often involve force data.